A 'new life' story or 'delaying the inevitable'? Exploring older people's narratives during exercise uptake. (March 2015) - Hudson, J.; Day, M.C.; Oliver, E.J.
Abstract: Objectives: The purpose of this study was to examine narratives of ageing in a clinical population embarking on a physical activity/exercise programme, exploring if and how their narratives changed throughout their experiences. Design: The study employed a longitudinal narrative approach. Method: Participants were six sedentary individuals aged between 78 and 89 years who were enrolled on an exercise programme for older adults. During the course of the 32-week programme participants took part in multiple interviews focused on their attitudes towards physical activity and their physical self-perceptions and identity. A structural narrative analysis was used to focus on the progression of the plot outlined in each participant's story. Results: Our results suggested the emergence of two comparative narratives, with each demonstrated in the stories told by three participants. The first narrative is one of decelerated decline, in which the exercise programme is assimilated or fitted into the existing life narrative, but little is made of the personal meaning of being active. In the second narrative, participation in exercise prompted participants to re-story their ageing narratives, changing from initially accepting the decline they associated with an ageing body, to the prospect of gaining some control. While this increased sense of control may intuitively seem positive, participants initially described a number of existential challenges and dilemmas as well as their resolution of these. Conclusion: Participants' emergent stories highlighted that while older adults may perceive exercise positively, their existing narratives of decline may be resistant to change. Where changes do occur, it is important for health professionals to recognize the associated difficulties with gaining increased responsibility for health. Highlights: We examine narratives of ageing in a clinical population embarking on a physical activity/exercise programme. Two comparative narratives were found. One narrative reflected decelerated decline in which the exercise programme was assimilated into the existing life narrative. In the second narrative participants re-storied ageing narratives, changing from accepting decline to the gaining control. Gaining control brought with it existential challenges and dilemmas as well as resolution.